2015
DOI: 10.1002/anie.201506469
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Size Control of Liquid‐Metal Nanoparticles under Ultrasonication

Abstract: This paper describes the reversible control of the size of liquid-metal nanoparticles under ultrasonication. Gallium was utilized as a liquid metal, which has a melting point of 29.8 °C. Investigating the effects of ultrasonication (power, time, and temperature) on the formation of gallium nanoparticles revealed that the process is similar to the formation of oil in water (O/W) or water in oil (W/O) emulsions, as the temperature significantly affects the size of the gallium nanoparticles (GaNPs). Under ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
166
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(176 citation statements)
references
References 43 publications
8
166
0
2
Order By: Relevance
“…LMs such as gallium, gallium-indium eutectic alloys (EGaIn: 75% Ga, 25% In (wt wt −1 )), and gallium-indium-tin alloys (Galinstan: 68.5% Ga, 21.5% In and 10% Sn (wt wt −1 )), with melting points of 29.8, 15.7 and 10.7 °C, respectively, have received increasing attention because they are generally chemically stable and do not react with water at room temperature. In addition, previous studies have shown that such alloys are safe for humans under normal circumstances345678910. Currently, there is a significant interest towards the chemical345 and morphological characterization of these emerging LMs56789.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…LMs such as gallium, gallium-indium eutectic alloys (EGaIn: 75% Ga, 25% In (wt wt −1 )), and gallium-indium-tin alloys (Galinstan: 68.5% Ga, 21.5% In and 10% Sn (wt wt −1 )), with melting points of 29.8, 15.7 and 10.7 °C, respectively, have received increasing attention because they are generally chemically stable and do not react with water at room temperature. In addition, previous studies have shown that such alloys are safe for humans under normal circumstances345678910. Currently, there is a significant interest towards the chemical345 and morphological characterization of these emerging LMs56789.…”
mentioning
confidence: 99%
“…In addition, previous studies have shown that such alloys are safe for humans under normal circumstances345678910. Currently, there is a significant interest towards the chemical345 and morphological characterization of these emerging LMs56789. Furthermore, as opposed to mercury and solid metals such as gold or silver nanoparticles whose optical properties have been extensively investigated, those of promising LMs have not been sufficiently explored11121314.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Proses ultrasonikasi memang merupakan teknik unggul dalam menghasilkan partikel berukuran nanometer (Yamaguchi, Mashima, dan Iyoda 2015). Namun demikian dalam proses ini akan terbentuk panas tinggi yang dapat mempengaruhi karakteristik bahan yang diproses.…”
Section: Pendahuluanunclassified
“…Tahap selanjutnya adalah peningkatan ukuran gelembung akibat proses difusi larutan kedalam gelembung dan dilanjutkan dengan tahap ketiga pecahnya gelembung saat ukurannya telah mencapai maksimal. Pecahnya gelembung ini dapat meningkatkan suhu sekitar gelembung hingga 5000 K (4727 °C) dan tekanan hingga ratusan atmosfer (Yamaguchi, Mashima, dan Iyoda 2015). Kondisi ekstrim ini dapat menyebabkan putusnya ikatan kimia bahanbahan yang ada di sekitar gelembung.…”
Section: Pendahuluanunclassified